ICT, young people and social work: distances and opportunities. - de Lucas y Murillo de la Cueva, Fernando; D'Antonio Maceiras, Sergio (Social Work Education, 2020)
The relationship between social work and Information and Communication Technologies (ICTs) is an awkward one in Spanish tradition, particularly from social work perspective due to a certain lack of institutional and professional competence in terms of understanding the capabilities of ICTs. Young people use ICTs to connect to each other and express themselves, however. ICTs represent a means—increasingly the main one—for young people to build and communicate their own identities and understand reality. As with other social sciences, social work suffers from a difficult relationship with young people. Youth is often studied differently and sometimes perceived as a problem that ends when adulthood is reached. In this context, the relationship among ICTs, social work and young people is also a difficult one. But this problem may also be a solution. By adopting a critical ICT approach, social work can create innovative initiatives and frameworks to improve communication between social work practitioners and teachers as with young people and students. Imagination and empathy will clearly be key to achieving this, in addition to deeper involvement in the use of new software and applications that can offer enhanced communication and build bridges between social workers and young people.